Stability Analysis of a Cantilevered Plate in Randomly Fluctuating Flow. (2016) - Kumar, S. Krishna; Gupta, Sayan
Abstract: Elastic structures like thin plates oscillating in fluid flow are susceptible to instabilities like flutter. The fluid-structure interaction between plate and the flow causes self-sustaining oscillations when the axial flow velocity exceeds a critical value. Such oscillations can be of very high amplitude and can be detrimental to structural safety. On the other hand, recent studies have revealed the possibility of energy being harvested from such oscillations. In either case, knowledge of the stability boundary of the system is crucial for appropriately designing the system. Most existing approaches in this regard consider the flow to be steady and hence do not accurately reflect the real life scenario where fluid flow is accompanied by random fluctuations. This study focuses on characterizing the response when the flow is accompanied by random fluctuations, which would serve as a first step in obtaining the stability boundaries. The fluctuating flow is modelled using Karhunen Loeve expansion (KLE) and the response is constructed using Polynomial Chaos expansion (PCE). Stochastic collocation approach has been employed for obtaining the PCE coefficients. The results are validated using Monte Carlo simulations.